ONLINE LEARNING IN OCCUPATIONAL HEALTH AND SAFETY COURSE DURING THE COVID-19 PANDEMIC, FACULTY OF ALLIED HEALTH SCIENCES, NORTHERN COLLEGE, TAK PROVINCE - Pimnumyen, Suwech (Pathumthani University Academic Journal, 2022)
The purposes of this classroom action research were to study the opinions and behaviors of students on online learning during the COVID-19 Pandemic and evaluate to lecturer quality in occupational health and safety course, semester 1/2564. The target population refers to 34 students of the Faculty of Allied Health Sciences, Northern College, they were study in occupational health and safety course, semester 1/2564 (During June - October 2021). The research instrument was online questionnaire. The content validity was checked by 3 experts, The Index of Item-Objective Congruence: IOC ≥ .67. The reliability was conducted using Cronbach’s alpha coefficient at .86. The parameters used to data analysis were frequency, percentage, mean and standard deviation. The results found that the majority of the students used their smartphones for online learning (67.60%) and for took the exam (55.90%). The students' opinions on the online learning were at very good level. The most consistent online learning behavior of students (67.60%) were completing the online exercises in time. The lecturer was evaluated by students at a very good level. The benefit of online learning program is that students can review the content of the course. However, the problem with the online learning process was the unstable internet signal that effect on students using online multimedia.